Massage Therapy in Outpatient Cancer Care: A Metropolitan Area Analysis - Virginia S. Cowen PhD, LMT; Robin Streit Miccio MS, LMT; Bijal Parikh MD (SAGE Publishing, 2017)
Massage offers cancer patients general quality of life benefits as well as alleviation of cancer-related symptoms/cancer-treatment-related symptoms including pain, anxiety, and fatigue. Little is known about whether massage is accessible to cancer patients who receive treatment in the outpatient setting and how massage is incorporated into the overall cancer treatment plan. Outpatient cancer centers (n = 78) in a single metropolitan area were included this mixed-methods project that included a systematic analysis of website information and a telephone survey. Massage was offered at only 40 centers (51.3% of total). A range of massage modalities were represented, with energy-based therapies (Reiki and Therapeutic Touch) most frequently provided. Although massage therapists are licensed health care providers in the states included in this analysis, massage was also provided by nurses, physical therapists, and other health care professionals.